Pandangan Al Zamakhshshari Tentang Ayat-Ayat Pluralisme Dalam Tafsir Al-KasshaF - Achmad Zainul Arifin; Wina Valestin Valestin (LPPM Institut Pesantren KH. Abdul Chalim, 2018)
Pluralism is the most beautiful gift and sunnatullah that must be accepted in this life. In reality a country must have diversity in terms of ethnicity, culture, and even religion and Indonesia is a country with the highest application of pluralism in the world. That the country of Indonesia is a country formed from cultural, ethnic and diverse religious diversity not only one culture or one religion. Creating plurality or diversity is one of God's will, so God also creates various kinds of concepts so that plurality itself does not collide with each other even if there is a clash, then it can be resolved properly. Even in the Qur'an the plurality is highly valued, in the Qur'an there are also many verses that explain plurality. Starting from how pluralism is created, then recognizing the existence of something diferent from what is belived to appreciate any differences that exist. In the Qur'an there are guidelines in living a good life therefore Muslims are encouraged to learn and apply what is in it. Especially in understanding differences that in essence is the will of God. One of Al Zamakhsha>ri>'s opinions in his book, Al Kasyaf's interpretation, says that Allah creates a difference in this life so that people can know each other and not get caught up in their own stupidity then compete in terms of goodness.